A generic algorithm for three-dimensional multiphase flows on unstructured meshes. (September 2018) - Manik, Jai; Dalal, Amaresh; Natarajan, Ganesh
Highlights: A balanced and consistent algorithm on hybrid unstructured meshes is proposed for multi-phase flow. Algebraic volume of fluid method is used for capturing the fluid interface. Least squares procedure is adopted for calculating all the gradient quantities. Apart from force balancing, consistency is also needed for convection dominant flows. Abstract: Binary fluid flows distinguished by high-density ratio are of practical importance to many of the engineering applications. Numerical simulations of such flows having sharp discontinuities across the interface is a challenging task and may lead to the generation of spurious velocities if proper care is not taken during discretization. In this regard, we present a consistent and balanced–force algorithm for binary fluid flows with very large density ratios using algebraic volume of fluid technique over three-dimensional hybrid unstructured meshes using a collocated framework. The algorithm emphasizes on the proper force balancing needed at the discrete level and also on the importance of consistent numerical treatment of similar terms across the equations. The efficacy of the formulation is demonstrated through extensive numerical experiments involving strong surface tension and/or gravitational forces. The results clearly indicate the importance of enforcing discrete balance of forces and ensuring consistent treatment of mass and momentum for robust and accurate simulations of multiphase flows.